SIN-like pathway kinases regulate the end of mitosis in the methylotrophic yeast ogataea polymorpha - Maekawa, Hiromi; Jiangyan, Shen; Takegawa, Kaoru; Pereira, Gislene (Cells, 2022)
The mitotic exit network (MEN) is a conserved signalling pathway essential for the termination of mitosis in the budding yeast Saccharomyces cerevisiae. All MEN components are highly conserved in the methylotrophic budding yeast Ogataea polymorpha, except for Cdc15 kinase. Instead, we identified two essential kinases OpHcd1 and OpHcd2 (homologue candidate of ScCdc15) that are homologous to SpSid1 and SpCdc7, respectively, components of the septation initiation network (SIN) of the fission yeast Schizosaccharomyces pombe. Conditional mutants for OpHCD1 and OpHCD2 exhibited significant delay in late anaphase and defective cell separation, suggesting that both genes have roles in mitotic exit and cytokinesis. Unlike Cdc15 in S. cerevisiae, the association of OpHcd1 and OpHcd2 with the yeast centrosomes (named spindle pole bodies, SPBs) is restricted to the SPB in the mother cell body. SPB localisation of OpHcd2 is regulated by the status of OpTem1 GTPase, while OpHcd1 requires the polo-like kinase OpCdc5 as well as active Tem1 to ensure the coordination of mitotic exit (ME) signalling and cell cycle progression. Our study suggests that the divergence of molecular mechanisms to control the ME-signalling pathway as well as the loss of Sid1/Hcd1 kinase in the MEN occurred relatively recently during the evolution of budding yeast.
This article belongs to the Special Issue Comparative Biology of Microtubule Organization in Eukaryotes
Gesehen am 17.06.2022